Efficient thermal properties enhancement to hyperbranched aromatic polyamide grafted aluminum nitride in epoxy composites. (22nd January 2013) - Qian, Rong; Yu, Jinhong; Xie, Liyuan; Li, Yanan; Jiang, Pingkai
Abstract : Aluminum nitride (AlN) nanoparticles were firstly treated with a silane coupling agent, γ‐aminopropyl‐triethoxysilane (γ‐APS), to introduce amine groups (AlN‐APS), then grafting of the hyperbranched aromatic polyamide started from the modified surface (AlN‐HBP). The surface modified AlN nanoparticles were characterized by Fourier transform infrared, nuclear magnetic resonance, and thermogravimetric analyzer. Then the nanoparticles with these three different interface structures were selected as reinforcing fillers for epoxy composites. The study reports the influence of interfacial structure of nanoparticles on the morphology and thermal properties of epoxy composites. It was found that the AlN‐HBP nanoparticles result in a strong interface and thus the incorporation of the AlN‐HBP nanoparticles not only improved the dispersion of the nanoparticles in the epoxy matrix but also enhanced the thermal conductivity, thermal stability, glass transition temperatures, and dynamical thermomechanical properties. Copyright © 2013 John Wiley & Sons, Ltd.